2009
DOI: 10.1093/ndt/gfp062
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic differences in cephalic arch geometry for diabetic and non-diabetic ESRD patients

Abstract: Based on this study, it was found that there are two distinct types of cephalic arch geometries. Patients having diabetes mellitus show a significant probability of having a larger R/d ratio and wider arch angle. This study has given insight into structural alterations in geometry of the cephalic arch of diabetics with brachiocephalic fistula access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 20 publications
0
22
0
5
Order By: Relevance
“…Cephalic arch stenosis is presumed secondary to the course of the vein within the deltopectoral groove. 14 In addition, repeated punctures to access the AVF during HD treatments also leads to vessel injury and continued dilatation, eventually leading to aneurysmal formation. 9…”
Section: Discussionmentioning
confidence: 99%
“…Cephalic arch stenosis is presumed secondary to the course of the vein within the deltopectoral groove. 14 In addition, repeated punctures to access the AVF during HD treatments also leads to vessel injury and continued dilatation, eventually leading to aneurysmal formation. 9…”
Section: Discussionmentioning
confidence: 99%
“…Low aspect ratio constrictions appear to be common in stenotic flows. For example, a review by Hammes et al 26 found that stenoses often have widths close to the vessel diameter.…”
Section: A Constriction Modelmentioning
confidence: 99%
“…Despite this, a lower than predicted incidence of diabetes in those with cephalic arch stenosis has been a consistent finding in multiple other studies [5,20,15]. Hammes et al have proposed that patients with diabetes have a wider cephalic arch than those without, thus reduced haemodynamic stress in this area [21]. Certainly it appears that the tight angle of the cephalic arch, with localised turbulent flow, may play an overwhelming role in the development of stenosis, overwhelming traditional risk factors implicated in vascular stenosis formation.…”
Section: Discussionmentioning
confidence: 67%